“March Myths” and the Communicative Memory of Polish Society - Czyżewski, Andrzej (Sensus Historiae, 2023)
The text aims to critically analyse the myths surrounding the events of March ‘68 in Poland. The starting point here is the assumption taken from the field of memory studies, according to which myth is not a synonym for falsehood, but a neutral category for describing the social dimensions of remembering. In the first part of the text, the author focuses on the reconstruction of the most important – in his opinion – “March myths”. The second part of the text contains an analysis of over forty narrative interviews with the participants of March ‘68 in Łódź, which becomes a pretext for a broader reflection on mutual relations between myths and the communicative memory of the representatives of the ‘68 generation. The author tries to answer, among others, the following research questions: What types of “March myths” did and do dominate the narratives about these events? In what sense and to what extent can we talk about specific elements of the communicative memory of the “extra-Varsovian” participants of March ‘68?